Adsorption characteristics of droplets applied on non-smooth leaf surface of typical crops - Shujie, Wang; Hujun, Wang; Chun, Li; Xiangmei, Zhong; Hui, Huang; Yajun, Zhou (International Journal of Agricultural and Biological Engineering, 2016)
To further understand the adsorption characteristics of different-type leaf surfaces adsorbing pesticide droplets and reveal the adsorption mechanism of pesticide droplets on non-smooth leaves, non-smooth leaves of 12 kinds of typical target plants were investigated in this study. The parameters of surface morphological characteristics were measured, which include contact angle between leaves and water droplets, water holding capacity surface tension, polar component, dispersion component and other quantitative range of indicators and variation by modern means. The relationships between the indicators and water holding capacity were investigated respectively. The experimental results show that the number of trichomes, epidermal wax, morphology and distribution characteristics have influences on adsorption characteristics of the water droplets. There is a negative correlation between free energy of obverse side and the water holding capacity (R=−0.447) while the free energy of reverse side and the water holding capacity show a positive correlation (R=0.212). Also, there is a negative correlation between polar component of obverse side and the water holding capacity (R=−0.357) while the polar component of reverse side and the water holding capacity in plant leaves show a positive correlation (R=0.149). The research can provide a scientific theory for reasonable spraying of pesticide in the agricultural production, and can be a reference for the development of pesticide adjuvants and bionic pesticides.Keywords: surface of plant leaves, adsorption characteristics, contact angle, water holding capacity, surface tensionDOI: 10.3965/j.ijabe.20160901.1022Citation: Wang S J, Wang H J, Li C, Zhong X M, Huang H, Zhou Y J. Adsorption characteristics of droplets applied on non-smooth leaf surface of typical crops. Int J Agric & Biol Eng, 2016; 9(1): 35－41.